Switchable molecular tweezers: design and applications - Msellem, Pablo; Dekthiarenko, Maksym; Hadj Seyd, Nihal; Vives, Guillaume (Beilstein Journal of Organic Chemistry, 2024)
Switchable molecular tweezers are a unique class of molecular switches that, like their macroscopic analogs, exhibit mechanical motion between an open and closed conformation in response to stimuli. Such systems constitute an essential component of artificial molecular machines. This review will present selected examples of switchable molecular tweezers and their potential applications. The first part will be devoted to chemically responsive tweezers, including stimuli such as pH, metal coordination, and anion binding. Then, redox-active and photochemical tweezers will be presented.
Keywords: coordination; molecular recognition; molecular switches; photoswitch; redox; supramolecular chemistry